AdamAdelia Inventory Management System - Sabarudin, Nur Asiyah Nabilah; Hamid Ali, Dr Firkhan Ali (Applied Information Technology And Computer Science, 2025)
The AdamAdelia Inventory Management System is a cutting-edge solution to revolutionize inventory management practices at AdamAdelia’s Kids Clothes Shop. It addresses unique challenges children’s apparel stores face, such as managing ever-changing fashion trends and ensuring the timely availability of products. This system enhances user-friendliness and efficiency by providing real-time insights, automating restocking processes, and facilitating seamless inventory updates. Doing so aims to increase profitability and drive success in the competitive retail landscape. Tailored specifically for AdamAdelia’s Kids Clothes Shop, the system offers adaptability for any retail business with similar inventory management challenges. The projected timeline ensures immediate optimization of day-to-day operations upon deployment, integrating smoothly into existing workflows. Key features include real-time stock tracking, automated restocking recommendations based on sales data and consumer preferences, and robust security measures to safeguard sensitive data. A feedback mechanism and thorough usability testing ensure the system remains user-centric, minimizes errors, and enhances employee productivity. The AdamAdelia Inventory Management System aims to drive efficiency, increase profitability, and elevate the shop’s success by providing a comprehensive, user-centric solution.